Female influencers: Analyzing the social media representation of female subjectivity in Italy - Roberti, Geraldina (Frontiers in Sociology, 2022)
The paper addresses the representation of female subjectivity on social media, highlighting how such women images have a significant impact on the gendered narratives and discourses that populate the public sphere. The article analyzes specifically the pattern of femininity represented by female influencers and the bond they are able to establish with their followers. Starting from the notion of postfeminism sensitivity, it highlights how these celebrities embody its ideals in terms of self-realization, independence and empowerment. Finally, the figures of two of the most popular social media influencers in Italy, Chiara Ferragni and Benedetta Rossi, are analyzed, highlighting their ability to represent a successful model of female digital entrepreneurship.